Heat transfer coefficient of flowing wood pulp fibre suspensions to monitor fibre and paper quality. (5th March 2015) - Kazi, S.N.; Duffy, G.G.; Chen, X.D.
Abstract: Heat transfer measurements were obtained for a range of suspensions of wood pulp fibre flowing through a pipeline. Data were generated over a selected range of flow rates and temperatures from a specially built flow loop. It was found that the magnitude of the heat transfer coefficient was above water at equivalent experimental conditions at very low fibre concentrations, but progressively decreased until it was below water at slightly higher concentrations. It was found that the heat transfer was affected by varying fibre properties, such as fibre length, fibre flexibility, fibre chemical and mechanical treatment, the variation of fibres from different parts of the tree as well as the different pulping methods used to liberate the fibres from the wood structure. Heat transfer coefficient was decreased with the increasing of fibre flexibility as found by previous workers. In the present investigation properties of fibre and paper are correlated with heat transfer to suspensions of fibres. Variations in fibre characteristics can be monitored in flowing suspension of fibres by measuring heat transfer coefficient and using those measurements to adjust the degree of fibre refining treatment so that papers made from those fibres are more uniform, more consistent and within product specification. Highlights: Heat transfer to natural fibre suspensions is governed by fibre properties and velocity. Heat transfers to fibre suspensions are affected by the fibre manufacturing methods. Heat transfers are affected by the degree of chemical and mechanical treatment of fibres. Heat transfer coefficient decreases with increasing of fibre flexibility. Heat transfer to fibre suspensions could be correlated with the fibre and paper properties.